Understanding the impact of Achilles lipid content on tendon mechanical parameters: a cross-sectional study of people with familial hypercholesterolemia and healthy controls - Kipling Squier; Charlie Waugh; Joanne Callow; Wayne Patola; Michael A. Hunt; Liam R. Brunham; Jennifer Jakobi; Alexander Scott (BMC Musculoskeletal Disorders)
Abstract Background Familial hypercholesterolemia (FH) is a genetic condition that affects cholesterol metabolism, resulting in life-long elevated serum levels of low-density lipoprotein cholesterol. Systemically elevated cholesterol levels are associated with the onset of tendon injury and potentially lead to impaired mechanical properties. Applying a cross-sectional design, we examined whether FH patients present with altered Achilles biomechanics compared to healthy controls and conducted correlational analyses to determine the relationship between Achilles tendon biomechanics and tendon lipid or water content. Methods Patients with FH (n = 33) and healthy controls (n = 31) were recruited from the Greater Vancouver area. Achilles cross sectional area, thickness, lipid and water content was determined using Dixon method magnetic resonance imaging (3.0T). Achilles mechanical properties were determined using synchronized dynamometry, motion capture, ultrasound and electromyography during ramped maximal voluntary isometric contractions, and stiffness and Young’s modulus calculated. Between group differences were assessed with independent t-tests or Mann-Whitney U tests and Pearson’s r or Spearman’s ρ were employed for correlational analyses. Sensitivity analysis was conducted on FH patients diagnosed with Achilles xanthoma and the remaining FH patients. Results FH patients had significantly elevated Achilles total water content (p = 0.006), cross-sectional area (p = 0.006), and thickness (p = 0.019). No between-group differences were observed in any of the biomechanical parameters. In patients with FH there were significant positive relationships between tendon lipid or water content and tendon strain (ρ = 0.35, p = 0.046; r = 0.42, p = 0.02, respectively). No significant relationships were observed in control participants. In patients with FH, increased tendon cross-sectional area was associated with reduced stiffness (r=-0.371, p = 0.033) and increased strain (r = 0.48, p = 0.005). The presence of xanthoma was associated with increased Achilles dimensions (p < 0.05), total water content (p = 0.03), strain (p = 0.029), and decreased Young’s modulus (p = 0.001). Conclusion Increased Achilles lipid and water content is associated with increased tendon strain in people with FH and the presence of xanthoma might indicate altered tendon mechanics. This study holds relevance for individuals with hypercholesteremia, as best management practices advocate for physical activity as part of a healthy lifestyle.